The role of well-child visits in detecting developmental delay in preschool children - M. Moser; C. Müllner; P. Ferro; K. Albermann; O. G. Jenni; M. von Rhein (BMC, 2023)
Abstract Background Early detection of developmental delay (DD) in preschool children is crucial for counselling parents, initiating diagnostic work-up, and starting early intervention (EI). Methods We conducted a register study of all preschool children referred for EI in the Canton of Zurich, Switzerland, in 2017 (N = 1,785) and used an online survey among primary care physicians (PCPs, N = 271) to evaluate the care service of DD children. Results PCPs accounted for 79.5% of all referrals by physicians and had correctly referred over 90% of the children in need of EI at an average age of 39.3 months (SD 8.9). In the survey, which represents 59.2% of all pediatricians and 11.3% of all general practitioners in the Canton, PCPs reported performing a mean of 13.5 (range 0-50, SD 10.7) well-child visits per week to preschool children and estimated well-child visits to be the most frequent type of consultation (66.7%) for the identification of DD. Parents' hesitancy in accepting further evaluation or support were reported by 88.7%. Conclusions Most preschool children with DD are identified in well-child visits. These visits represent an ideal opportunity for early detection of developmental impairment and initiation of EI. Carefully addressing parents' reservations could reduce the rate of refusal, thus improving early support for children with DD.